Plunging into the sea: Ideological change, institutional environments and private entrepreneurship in China - Massimo Bordignon; Yanhua Deng; Jian Huang; Jin Yang (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
This paper examines the integration of Chinese Communist Party membership and private entrepreneurship in China after 2002, when the Party revised its constitution and officially removed ideological discrimination against private entrepreneurs. Using six waves of a nationwide survey of privately owned enterprises in China from 1997 to 2008, we find that the constitutional change led to an exodus of Party members, and particularly senior officials, into the private sector. On the contrary, very few private entrepreneurs were admitted to the Party. The exodus of Party members was more prominent in regions with weaker market-supporting institutions. After the reform, Party affiliation is also shown to provide considerable private benefits to entrepreneurs, in the form of easier access to loans from state owned banks, reduced government expropriation, improved firms' performance. These political rents were larger in regions with weaker market-supporting institutions.
Keywords: H1; P26; 330; Party membership; private entrepreneur; ideology; market institutions; political rents